TRANSFORMING EXTENDED ENTITY-RELATIONSHIP MODEL INTO OWL ONTOLOGY IN TEMPORAL DATABASES - Vo, Minh Hoang Lien; Hoang, Quang (Journal of Computer Science and Cybernetics, 2018)
Many previous systems were built based on the ER model, so the upgrading and transforming the ER model into ontology for reducing cost is really necessary. There are several studies aim at transforming from ER and EER model into ontology. However, these studies have not classified the semantic of the recursive relationship in ER model, so the semantic of the recursive relationship will be easily lost during the transformation. Also, the studies have not mentioned the designing of the ontology that supports temporal attributes based on the temporal ER model. This paper discusses the semantic classification of the recursive relationship and TimeER model (extended EER in temporal databases) and OWL ontology. And propose a method to transform into OWL ontology.